The Places Where Community Is Practiced How Store Owners and Their Businesses Build Neighborhood Social Life - Steigemann, Anna (Stadt, Raum und Gesellschaft,, 2019)
In this open access publication, the social cohesion of urban neighborhoods and their residents is examined, which is often viewed as vulnerable since increased mobility, individualization, wider socio-economic and demographic changes have fundamentally altered the basis for everyday social interaction in urban neighborhoods. Anna Steigemann gives scholarly attention to the concrete places where neighborly interactions still take place and to how these interactions affect local community building. She illuminates and explores the ordinary everyday interactions and social practices in and around shops and gastronomic facilities on a shopping street in Berlin-Neukölln, revealing how these businesses are important places where community is practiced, but also why they are increasingly threatened by commercial and residential gentrification. Contents Social Life and Trade on a Metropolitan Shopping Street Sensitizing Theoretical Concepts and Social Practice Approach Ethnographic Research Design for the Study of Local Businesses The Social and Spatial Context of the Case Businesses Businesses as Third Places Store Owners on a Gentrifying Street: Public Characters that Offer "More" Target Groups Researchers and students in the fields of urban studies, urban sociology, geography, and planning Practitioners and decision-makers in the fields of urban-planning , urban and local economic development The Author Dr. Anna Steigemann is an Urban Sociologist and works as an Assistant Professor at the Chair of International Urbanism and Design at Technical University Berlin. .